2017
DOI: 10.1002/2017jd026525
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Wet Troposphere Delays Over Inland Water Bodies

Abstract: Satellite radar altimetry has enabled the study of water levels in large lakes and reservoirs at a global scale. The upcoming Surface Water and Ocean Topography (SWOT) satellite mission (scheduled launch 2020) will simultaneously measure water surface extent and elevation at an unprecedented accuracy and resolution. However, SWOT retrieval accuracy will be affected by a number of factors, including wet tropospheric delay—the delay in the signal's passage through the atmosphere due to atmospheric water content.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A complete error budget should also take into account errors expected from satellite orbit, signal delay from the troposphere, vegetation effects and wind effects on the radar backscattering from water [39,40]. Wet tropospheric delays on the radar return have been analysed in details by Mehran et al [26] over inland reservoirs of souhtwest US and have been found to be between 4 and 18 mm, depending on climatic conditions, elevation and surface area of the reservoir. Given the high content in the tropospheric water vapor during the monsoon season [25], tropospheric effects on the delay of the radar signal in the Sahel are supposed to be in the highest range of the values reported in [26].…”
Section: Concluding Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete error budget should also take into account errors expected from satellite orbit, signal delay from the troposphere, vegetation effects and wind effects on the radar backscattering from water [39,40]. Wet tropospheric delays on the radar return have been analysed in details by Mehran et al [26] over inland reservoirs of souhtwest US and have been found to be between 4 and 18 mm, depending on climatic conditions, elevation and surface area of the reservoir. Given the high content in the tropospheric water vapor during the monsoon season [25], tropospheric effects on the delay of the radar signal in the Sahel are supposed to be in the highest range of the values reported in [26].…”
Section: Concluding Discussion and Perspectivesmentioning
confidence: 99%
“…The objective of the present study is to assess the potential of SWOT for monitoring water volumes in Sahelian ponds and lakes. The Sahelian region can be challenging for remote sensing given the poorly documented and highly variable values in surface characteristics (water roughness, soil type and soil moisture) impacting the radar backscattering coefficients [23,24] and the wide range of atmospheric moisture content [25] that can affect the propagation of electromagnetic waves in the atmosphere [26]. Simulations can be used to investigate some of these issues before launch.…”
Section: Introductionmentioning
confidence: 99%
“…Research on SWOT hydrology is still in pre-study and verification stages. Most of previous studies have focused on rivers (Biancamaria et al, 2016;Durand et al, 2008Durand et al, , 2014Durand et al, , 2016Durand et al, , 2020Frasson et al, 2017;Gejadze and Malaterre, 2017;Häfliger et al, 2019;Hagemann et al, 2017;Mehran et al, 2017;Moramarco et al, 2019;Munier et al, 2015;Oubanas et al, 2018;Pavelsky et al, 2014;Yoon et al, 2012), and relatively few studies have focused on lakes (Bergeron et al, 2020;Biancamaria et al, 2010Biancamaria et al, , 2016Grippa et al, 2019;Lee et al, 2010). Lee et al (2010) took lakes in three high-latitude areas as research objects, simulated SWOT lake level heights using radar altimetry and in situ data and then combined the heights with image data to study the changes in water storage.…”
mentioning
confidence: 99%